Hiking Canyonlands and Arches National Parks 2023 : a guide to 64 great hikes in both parks - Schneider, Bill (FalconGuides, 2023)
"Features the best hikes in the Canyonlands and Arches National Parks. Includes hikes for a variety of skill sets and distances, from day hikes to extended trips, with photographs, can't-miss views, and specs for each trail"--